Finance, investment and economic development - Blackman, Courtney N. ([CCMS] [St. Augustine]TT, 2001)
Examines the inter-relationship between finance and investment with a view to formulating an appropriate policy-mix for the promotion of economic development in developing countries such as those of CARICOM